Assessing a Group of Physicians' Ethical Sensitivity in Turkey - M Çetin; M Cimen (Tehran University of Medical Sciences, 2011)
Background: The objective was to measure the sensitivity of a group of physicians regarding the ethics-related situations, which they faced during patient care and treatment. Methods: All of 306 physicians who joined the Turkish Army for compulsory military service in December 2008 were included in the study. A "Moral Sensitivity Questionnaire", formed by Kim Lutzen, was applied to all of them. Results: From total, 95% of physicians performed their job willingly, 88% of physicians attended ethic lessons (n=265), 72.4% (n=218) followed ethic publications, 67.4% (n=203) stated that there was an ethic committee at their institutions, and 5% worked as a member of the ethic committee. There were statistically significant differences between autonomy, benevolence meaning, conflict, and total scores according to workplace of physicians, employment period, and being specialists. Points of autonomy were found lower in physicians working at private hospital and health center than those at public hospital. Conclusion: Ethical sensitivity of physicians changed due to work place. We conclude that organizational arrangements are of beneficial effects to increase ethical sensitivity.